Evaluating the Impact of Blood Rheology in Hemodynamic Parameters by 4d Flow Mri in Large Vessels Considering the Hematocrit Effect - Castillo-Del Barrio, E (Elsevier Ltd, 2026)
Aortic hemodynamic parameters estimated from 4D Flow Magnetic Resonance (MR) velocity measurements are often estimated using a constant Newtonian viscosity, neglecting blood s shear-thinning behavior. The aim of this work is to estimate and assess whether Newtonian viscosity is sufficient to quantify these parameters, given the non-Newtonian nature of blood. Additionally, we demonstrate that shear-thinning effects remain observable in large vessels despite artifacts commonly present in 4D Flow MR images. To address this, we quantified the impact of blood rheology and hematocrit (Hct) on Wall Shear Stress (WSS), the rate of viscous Energy Loss (ĖL), and the Oscillatory Shear Index (OSI) based on velocity data obtained from 4D Flow MR images. Using a Hct-dependent power-law non-Newtonian model with experimentally derived rheological parameters, we analyzed these metrics across a broad range of Hct values at physiological temperatures in both in-silico and in-vivo MR datasets. The results reveal significant differences between Newtonian and non-Newtonian models. In in-silico experiments, WSS and ĖL differed by up to +189% and +112% at systole, with reductions of −74% and −80% at diastole, respectively, while OSI differences ranged from −23% to −30%. For in-vivo data, WSS and ĖL deviations reached −44% and −60% at systole, ranging from −69% to +73% at diastole, with OSI differences averaging −21%. These findings highlights the importance of accounting for non-Newtonian blood rheology when estimating hemodynamic parameters from 4D Flow MR images in large vessels, enhancing the accuracy of cardiovascular disease assessments using in-vivo aortic data. © 2025 Elsevier Ltd